(untitled) (Research, Society and Development, 2020)
The Covid-19 pandemic in different countries, particularly in terms of performing their duties and functions, has both direct and indirect implications on the judiciary. This paper calls for a contrast between the implementation of law emergencies in the United States and the judiciary’s reflection in Indonesia. The study uses the comparative approach in constitutional law to provide advice, which needs to be avoided in the Indonesian constitutional law by researching legal material and procedures in other countries’ constitutional law. This article concludes that the Law of Judicial Power and the Law of Procedure in Indonesia require strict legal material on how procedural law does not give delegates too much technical, regulatory authority to each court during the time of crisis and has the potential to create unequal policies in the future to deal with judicial emergencies so that regulation is necessary.